Innate Immunity in Diabetic Wound Healing: Focus on the Mastermind Hidden in Chronic Inflammatory - Geng, Kang; Ma, Xiumei; Jiang, Zongzhe; Huang, Wei; Gao, Chenlin; Pu, Yueli; Luo, Lifang; Xu, Youhua; Xu, Yong (Frontiers in Pharmacology, 2021)
A growing body of evidence suggests that the interaction between immune and metabolic responses is essential for maintaining tissue and organ homeostasis. These interacting disorders contribute to the development of chronic diseases associated with immune-aging such as diabetes, obesity, atherosclerosis, and nonalcoholic fatty liver disease. In Diabetic wound (DW), innate immune cells respond to the Pathogen-associated molecular patterns (PAMAs) and/or Damage-associated molecular patterns (DAMPs), changes from resting to an active phenotype, and play an important role in the triggering and maintenance of inflammation. Furthermore, the abnormal activation of innate immune pathways secondary to immune-aging also plays a key role in DW healing. Here, we review studies of innate immune cellular molecular events that identify metabolic disorders in the local microenvironment of DW and provide a historical perspective. At the same time, we describe some of the recent progress, such as TLR receptor-mediated intracellular signaling pathways that lead to the activation of NF-κB and the production of various pro-inflammatory mediators, NLRP3 inflammatory via pyroptosis, induction of IL-1β and IL-18, cGAS-STING responds to mitochondrial injury and endoplasmic reticulum stress, links sensing of metabolic stress to activation of pro-inflammatory cascades. Besides, JAK-STAT is also involved in DW healing by mediating the action of various innate immune effectors. Finally, we discuss the great potential of targeting these innate immune pathways and reprogramming innate immune cell phenotypes in DW therapy.